PENGARUH INTENSITAS PENEBANGAN DAN LERENG TERHADAP KETERBUKAAN TANAH - Jurnalis Thaib (Jurnal Penelitian Hasil Hutan, 1985)
Ground exposure is one of  the stand damages caused by logging. Logging  which generally do not comply with  the stipulation  of the Indonesian  Selective  Cutting (TPI) system,  have caused varying  degrees of ground  exposure as follows:On slopes of  0 - 25% where  the number of trees felled per hectare are 0 - 4,5 - 9 and 10 or up, ground exposure varied between 5.4 -13.8%,  13.4 - 22.5%,  and 20.9 - 26.6%  respectively.On slopes of  26% and up,  where  the number  of  trees felled per hectare are 0 - 4, 5 -  9 and 10 or up,  ground  exposure  varied between 7.6 - 13.8%, 11.9 - 19.7% and  17.1- 24.6% respectively.Dominant  factors in the process of ground  exposure  are management,  particularly  with regard to the organization of skidding and hauling activities,  and  the number  of  trees felled  per unit area. Unproductive  tractor movements  e.g. in locating logs,  increases ground  exposures and total cost per unit logs produced,  and should therefore  be avoided.